A study of using fuzzy logic based system for adaptation of precise insulin dosage for type II diabetes patients - Prima, Afroza Afrin (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.